Liability under post-tonsillectomy lethal bleeding of the tonsillar artery: A report of two cases. Issue 1 (January 2015) - Tuchtan, L.; Torrents, J.; Lebreton-Chakour, C.; Niort, F.; Christia-Lotter, M.A.; Delmarre, E.; Nicollas, R.; Piercecchi-Marti, M.D.
Abstract Post-operative haemorrhage is a frequent complication of tonsillectomy: a primary haemorrhage occurring in the first hours is rapidly dealt with by the surgical team. A secondary haemorrhage, which commonly occurs once the child has returned home, can be fatal if it is not dealt with quickly. We present two cases of a lethal outcome in children following a secondary post-tonsillectomy haemorrhage, for which the parents filed legal proceedings. Medical liability can be exercised during all stages of health care. Performing an autopsy associated with histological analyses is found to be indispensable for the identification of the causes of bleeding, as well as its mechanism.